DEVELOPMENT OF DOMICA MEDIA (DOMINO FRACTION) BASED ON LOCAL PRODUCTS TO IMPROVE NUMERACY IN GRADE IV OF ELEMENTARY SCHOOLS (JOSAR (Journal of Students Academic Research), 2025)
Ability numeracy is element important things to do mastered the Merdeka curriculum for help student in data analysis and retrieval decision , while knowledge about product local introduce they are in diversity culture and improve love to product domestically . The research method used is research and development of the ADDIE model. Data collection in study This that is interviews , questionnaires , and tests . The methods used in study This that is using ( RnD ). With amount 14 students at SDN 2 Sukorejo , 14 students at SDN 2 Gandusari , 6 students at SDN 2 Ngrayung , and 20 students at SDN 1 Wonorejo . The results of the research conducted that is the validity of Domica media is already worthy used . Expert validator results Material , Media, Language got an average of 96% “very good” and expert practitioner obtained 95% “Very Eligible”. Trial product carried out in two stages that is scale small and scale big . Questionnaire response student scale test small 94% “Very Interesting ”. Questionnaire response student scale big 96% “ Very Interesting ”, and the questionnaire teacher response scale large 96% “ Very Interesting . The use of Domica media is stated effective after the N-Gain test. The mean value test result is 61.39 or > 56. So it can be concluded effective use of Domica learning media For increase ability numeracy student grade 4 school base